The Design Canvas Platform on the Arena-O Startup Venture - Ramadhan, Muhammad Nuraga Lazuardy (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to plan a suitable business model using the Platform Design Canvas for the Arena-O Startup business. This study uses a qualitative method. Data collection was carried out by in-depth interviews and documentation study. The informants in this study represent the respective actors of the platform business, namely producers, consumers, and platform owners. The results of this study describe the business model of a sports field reservation startup called Arena-O, which is detailed using thirteen blocks on the Platform Design Canvas. Thus, thirteen blocks in this reseacrh are platform owners, stakeholder platforms, enabling services, empowering services, other services, core value proposition, ancillary value proposition, infrastructure and core components, transactions, channels & contexts, partners, peers producers, peers consumers. This research can find out the visualization of Arena-O’s business processes from upstream to downstream. Then from these results, the managerial implications of Enabling Services, Other Services, and Partners indicators can be applied to Arena-O so that it can develop.